Register‐based incidence of multiple sclerosis in Brittany (north‐western France), 2000–2001. (14th October 2014) - Yaouanq, J.; Tron, I.; Kerbrat, A.; Leray, E.; Hamonic, S.; Merienne, M.; Hinault, P.; Edan, G.
<x xml:space="preserve">Abstract</x> Objectives To report on multiple sclerosis (MS) incidence in Brittany, north‐western France. Materials & Methods From 2000, we set up a population‐based register for patients presenting a putative incident MS (PIMS), that is first symptoms compatible with MS onset. We used 3 medical sources of case ascertainment (neurologists, CSF, regional MS‐Clinic). Eligibility criteria required both clinical onset and being permanent resident of Brittany in 2000 or 2001. From 2010, all medical records were tracked, the 10‐year follow‐up allowing previously reported data to be updated. Results Of 313 eligible PIMS, there were 208 definite MS (both McDonald and Poser criteria), 41 CIS‐probable MS (Poser criteria), 32 CIS‐possible MS and 32 non‐MS. Our incident cohort of 249 MS cases with definite/probable MS (sex ratio 2.95) gave a crude annual incidence of 4.28 per 100, 000 inhabitants (6.22 for women, 2.23 for men), and age‐standardized rates (adjustment to the European population) of 4.41 [3.32–5.51], 6.68 [4.75–8.60], and 2.21 [1.12–3.31], respectively. Age‐specific rates by gender and initial course showed that attack onset MS peaked at 25–29 years and progressive onset MS at 40–44 years in women (20–24 years and 45–49 years in men, respectively). Conclusions Brittany is confirmed a high‐risk region for MS. Our data show marked differences in sex‐specific pattern of MS incidence by clinical course and point out 25‐ to 29‐year‐old women as having the highest MS risk. While temporal variations cannot be excluded, comparison with overall French data suggests that other factors rather than latitude may influence the MS risk in France.